2020
DOI: 10.4028/www.scientific.net/msf.998.114
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Kinetics of Polypropylene and High Density Polyethylene Wastes Using Kaolin Catalyst

Abstract: Plastic is materials that are not easily broken down, so it can cause a variety of complex problems such as loss of natural resources, environmental pollution, and depletion of landfill space. Plastic favored by the public is Polypropylene (PP) and High Density Polyethylene (HDPE) for example, food storage, transparent drinking glasses and drinking bottles for babies. This will be a problem in the future. Some alternatives used to reduce the volume of plastic waste are the thermal transformation process which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Oil produced with bentonite added not only produced higher yields but better physical properties, as well, compared to the oil produced with zeolite. The highest liquid yields of 100 wt.% for HDPE pyrolysis over bentonite (50 wt.%) and spent fluid catalytic cracking catalyst (FCC) were obtained by Elordi et al [92], and 99.82 wt.% for pyrolysis of low-density polyethylene (LDPE) on neat kaolin powder were obtained by Erawati et al [93]. The reviewed research reveals that Seliverstov et al [88] concluded that the modification of clay minerals (e.g., acid-washing or pillaring) was helpful to achieve a higher yield of the liquid fraction in some reviewed cases, but in others, pure clays also showed excellent catalytic activity.…”
Section: Other Fuel-related Applications Of Aluminosilicate Clay Mine...mentioning
confidence: 99%
“…Oil produced with bentonite added not only produced higher yields but better physical properties, as well, compared to the oil produced with zeolite. The highest liquid yields of 100 wt.% for HDPE pyrolysis over bentonite (50 wt.%) and spent fluid catalytic cracking catalyst (FCC) were obtained by Elordi et al [92], and 99.82 wt.% for pyrolysis of low-density polyethylene (LDPE) on neat kaolin powder were obtained by Erawati et al [93]. The reviewed research reveals that Seliverstov et al [88] concluded that the modification of clay minerals (e.g., acid-washing or pillaring) was helpful to achieve a higher yield of the liquid fraction in some reviewed cases, but in others, pure clays also showed excellent catalytic activity.…”
Section: Other Fuel-related Applications Of Aluminosilicate Clay Mine...mentioning
confidence: 99%